The Impact of the PQ4R Learning Method on Students’ Reading Comprehension Skills - Ratmiati; Mita Domi Fella Henanggil; Bunga Ratna Sari; Muspardi (Journal of Education Language and Innovation, 2026)
This research is motivated by the finding that students' reading comprehension ability is still relatively low. Out of 24 students, only 45% achieved mastery in the daily assessment, while 55% did not. The purpose of this study is to determine the effect of the application of the PQ4R learning method (Preview, Question, Read, Reflect, Recite, Review) on students' reading comprehension ability. The type of research used is quantitative with an experimental method, while the approach in this study uses a Pre-Experimental Design type One Group Pretest-Posttest Design. Data collection techniques used are tests and documentation. The population in this study were all 24 fifth grade students, and all of them were used as research samples. The instrument used was a multiple-choice test to measure students' reading comprehension ability. Data analysis was carried out using the t-test using the SPSS version 21 application. The results of the research findings indicate that there is an effect of the application of the PQ4R learning method on students' reading comprehension ability. This is indicated by an increase in the average score of students' posttest after the application of the PQ4R method. Based on the results of the t-test, a significance value of 0.000 <0.05 was obtained, so it can be concluded that H₀ is rejected and H₁ is accepted. Thus, it can be concluded that there is a significant influence of the application of the PQ4R learning method on the reading comprehension skills of fifth grade students at SDN 11 Tanjung Barulak.